1980
DOI: 10.1113/jphysiol.1980.sp013074
|View full text |Cite
|
Sign up to set email alerts
|

Potential clamp analysis of membrane currents in rat myelinated nerve fibres.

Abstract: SUMMARY1. Large myelinated nerve fibres were isolated from rats and the membrane action potential was recorded in single nodes of Ranvier. Potential clamp experiments were performed at 24 0C and in one fibre also at 33 0C.2. Positive potential steps were associated with an initial, mainly Na carried, current with an equilibrium potential (Ue) of 40+13 mV. The INa vs. U curve showed rectification at large positive potentials.3. The Na permeability (PNa) curve was characteristically S-shaped with a half value at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(97 citation statements)
references
References 21 publications
12
84
0
1
Order By: Relevance
“…We found a TTX-sensitive component restricted to the preterminal part of the endings whose time course (allowing for differences in temperature) closely agrees with that of the Na current reconstructed from voltage-clamp data by Chiu et al (1979) (Chiu et al 1979;Brismar, 1980). We failed to detect any TTX-sensitive component in membrane currents generated at the terminal part ofthe endings.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We found a TTX-sensitive component restricted to the preterminal part of the endings whose time course (allowing for differences in temperature) closely agrees with that of the Na current reconstructed from voltage-clamp data by Chiu et al (1979) (Chiu et al 1979;Brismar, 1980). We failed to detect any TTX-sensitive component in membrane currents generated at the terminal part ofthe endings.…”
Section: Discussionmentioning
confidence: 57%
“…However, recent reports on data obtained from mammalian nodes of Ranvier have shown that the repolarizing phase of the action potential depends mainly on Na inactivation and leakage conductance, the role of K conductance being negligible (Nonner & Stiimpfli, 1969;Chiu, Ritchie, Rogart & Stagg, 1979;Brismar, 1980; but see Binah & Palti, 1981). Similarly, only large diameter fibres from amphibian nerves seem to display a nodal delayed K conductance, while small ones appear devoid of it (Smith & Schauf, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 100 j, tmol/1 4-AP clearly enhanced the duration of the B-and C-fibre compound potentials in the isolated vagus nerve. The lack of effect on the vagus A-fibre potential may be explained by an absence of repolarizing potassium currents in these fibres as has been shown for single, rabbit (Chiu et al 1979) and rat (Brismar 1980) myelinated axons.…”
Section: A) 4-aminopyridinementioning
confidence: 73%
“…In these investigations the properties of sodium currents were found to be similar to those in 6-2 amphibian nerve fibres, whereas the potassium currents in fibres of warm-blooded animals were significantly smaller or even entirely lacking. More details on the kinetics and steady-state properties of sodium currents in mammalian nerve fibres were recently reported by Chiu, Ritchie, Rogart & Stagg (1979) for rabbit and by Brismar (1980) for rat. In their experiments the curve relating sodium permeability and membrane potential was found to be shifted by about 10 mV in the hyperpolarizing direction compared with amphibian fibres.…”
Section: Introductionmentioning
confidence: 99%